Design and Implementation of a Device to Measure and Read Heart Rate Using Arduino (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Heart rate monitoring is essential for assessing human health, especially in medical and fitness applications. This research focuses on the design and implementation of a heart rate measurement device using Arduino. The system utilizes a pulse sensor to detect heartbeats, an Arduino microcontroller for processing data, and an LCD display to present real-time heart rate readings. The device operates by capturing the photoplethysmography (PPG) signal from the fingertip and converting it into beats per minute (BPM). The proposed system is low-cost, portable, and easy to use, making it suitable for home and clinical applications. Experimental results indicate that the device provides accurate readings compared to standard medical equipment. Future improvements include integrating wireless data transmission and smartphone connectivity to enhance usability.